2020
DOI: 10.1101/2020.05.18.101857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leptospiral LPS escapes mouse TLR4 internalization and TRIF-associated antimicrobial responses through O antigen and associated lipoproteins

Abstract: 16 Leptospirosis is a worldwide re-emerging zoonosis caused by pathogenic Leptospira spp. All 17 vertebrate species can be infected; humans are sensitive hosts whereas other species, such as rodents, 18 may become long-term renal carrier reservoirs. Upon infection, innate immune responses are initiated 19 by recognition of Microbial Associated Molecular Patterns (MAMPs) by Pattern Recognition 20Receptors (PRRs). Among MAMPs, the lipopolysaccharide (LPS) is recognized by the 21 Toll-Like-Receptor 4 (TLR4) and a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 82 publications
3
12
0
Order By: Relevance
“…The production of the murine chemokine KC (CXCL1) was measured by ELISA 24 h p.i in the cellular supernatants. This chemokine was chosen as it was recently shown to be fully dependent on the MyD88-dependent signaling pathway ( 34 ), with MyD88 being the first main adaptor involved in TLR5-induced signaling ( 35 ). We therefore considered changes in KC secretion to be a good readout for analyzing TLR5 contribution to the leptospiral-induced signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of the murine chemokine KC (CXCL1) was measured by ELISA 24 h p.i in the cellular supernatants. This chemokine was chosen as it was recently shown to be fully dependent on the MyD88-dependent signaling pathway ( 34 ), with MyD88 being the first main adaptor involved in TLR5-induced signaling ( 35 ). We therefore considered changes in KC secretion to be a good readout for analyzing TLR5 contribution to the leptospiral-induced signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we assessed whether the lack of signaling through or escape of recognition by murine TLR5 is a species-specific phenomenon. Indeed, we previously highlighted PRR species-specificities of leptospiral MAMPs recognition, such as murine TLR4 receptor that only partially recognizes the leptospiral LPS ( 34 ), whereas human TLR4 does not. Conversely, human, but not the murine NOD1 is able to sense leptospiral muropeptides ( 17 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the fact that the human TLR4 does not significantly participate in leptospiral recognition could indicate a bacterial mechanism of avoiding recognition by the human immune system [37,39]. Interestingly, according to the recent in vitro study of Bonhomme et al [40], although leptospiral LPS is recognized by the murine TLR4, it avoids the TRIF adaptor arm of the TLR4 response. This may prove that pathogenic leptospires have evolved yet another immune evasion mechanism linked to their LPS.…”
Section: Leptospira Leptospirosis and Cross-talk Between Pathogenicmentioning
confidence: 99%
“…This may prove that pathogenic leptospires have evolved yet another immune evasion mechanism linked to their LPS. Further, Bonhomme and colleagues [40] suggest that the limited LPS recognition in mice could be the key to the chronicity of leptospires in rodents. In addition, LPS enables leptospires to adapt to temperature changes [41].…”
Section: Leptospira Leptospirosis and Cross-talk Between Pathogenicmentioning
confidence: 99%
“…Because the humoral response is believed to be directed mostly at the O antigen part of the LPS, we wondered whether the Icterohaemorrhagiae Verdun strain would have a shorter LPS like the M895 Manilae strain that also did not elicit strong responses(47). However our recent study showed that the Icterohaemorrhagiae Verdun LPS was similar in size to those of the Copenhageni and Manilae strains(60). Since the transient IgM and low IgG responses induced by the Verdun Cl3 strain mimicked either the heat-inactivated Manilae L495 strain, the L495 at low dose or the Patoc strain, and since mice showed no clinical signs upon Icterohaemorrhagiae infection, we also surmised that the Verdun Cl3 might have lost its virulence.…”
mentioning
confidence: 99%